Status Monitoring and Conservation Issues of Teinopalpus Imperialis Hope (Lepidoptera: Papilionidae), an Endangered Butterfly of Nepal - Khanal, Bhaiya; Shrestha, Keshab; Shrestha, Madan Krishna (Journal of Natural History Museum, 2015)
Teinopalpus imperialis an endangered swallowtail butterfly of high conservation value is encompassed into the Appendix II of CITES (Convention of International Trade of Endangered Species). This butterfly prefers its habitat at the altitudinal range of 2180 - 3000 m and emerges out for a brief period in summer months of May till July first week annually. This target species dwells in the broad leaved evergreen and mixed forest of Oaks (Quercus spp.). This specific work made an extensive study of Teinopalpus imperialis with respect to its population status, associated habitats and prevailing threats in Phulchoki Mountain (Lalitpur District), Nagarjun –Shivapuri National Park (Kathmandu District) and Nagarkot Mountain (Bhaktapur District). This revealed out the occurrence of 21 individual populations of this butterfly in the Phulchoki Mountain and 8 individuals in the Nagarjun forest. Nagarkot of Bhaktapur district did not represent any of this species due to prevailing high impact on its habitat area. J. Nat. Hist. Mus. Vol. 28, 2014: 49-56